Shift in The Meaning of Kanca Wingking in Javanese Society - Sigit Setyawan (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2024)
Women are considered kanca wingking, which means women must always be behind. Javanese women are considered weak creatures and must always be protected. Therefore, Javanese women must always obey what men say. Javanese women are not allowed to refuse or refute men's wishes, they must always obey men. This research is a qualitative descriptive research. The object of this research is constructing the meaning of kanca wingking in Javanese society. The data collection techniques used were observation and literature study. Based on the analysis that has been carried out, it can be concluded that the concept of kanca wingking in Javanese society cannot be separated from the influence of patriarchal culture. This culture is contained in the teachings of ancient Javanese texts written by the ancestors of the Javanese people. Currently, the concept of kanca wingking has experienced a shift in meaning where women are complementary and can help men fulfill their responsibilities. Women are now the place where ideas or concepts mature and have the right to play a role in decision-making.